Componential usage patterns in dengue 4 viruses reveal their better evolutionary adaptation to humans - Li, Gun; Shi, Liang; Zhang, Liang; Xu, Bingyi (Frontiers in Microbiology, 2022)
There were at least four types of dengue outbreaks in the past few years. The evolutionary characteristics of dengue viruses aroused great concerns. The evolutionary characteristics of dengue 4 viruses were studied in the present study based on their base usage patterns and the codon usage patterns. The effective number of codons and relative synonymous codon usage values of four types of dengue viruses were counted or calculated. The Kullback-Leibler divergences of relative synonymous codon usage from dengue viruses to humans, and the Kullback-Leibler divergences of amino acid usage pattern from dengue viruses to humans were calculated to explore the adaptation levels of dengue viruses. The results suggested that: 1) codon adaptation in dengue 4 viruses occurred through evolutionary process from 1956 to 2021, 2) overall relative synonymous codon usage values of dengue 4 viruses showed more similarities to humans than those of other subtypes of dengue viruses, 3) smaller Kullback-Leibler divergence of amino acid usage and relative synonymous codon usage from dengue viruses to humans indicated that the dengue 4 viruses adapted to human hosts better. All results indicated that both mutation pressure and natural selection pressure contributed to the codon usage pattern of dengue 4 viruses more obvious than to other subtypes of dengue viruses, and that the dengue 4 viruses adapted to human hosts better than other types of dengue viruses during their evolutionary process.